2021
DOI: 10.3389/fcvm.2021.795624
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome in COVID-19 Is Associated With an Aggravating Hypo-Responsive Platelet Phenotype

Abstract: Thromboembolic complications are frequently observed in Coronavirus disease 2019 (COVID-19). While COVID-19 is linked to platelet dysregulation, the association between disease outcome and platelet function is less clear. We prospectively monitored platelet activation and reactivity in 97 patients during the first week of hospitalization and determined plasma markers of platelet degranulation and inflammation. Adverse outcome in COVID-19 was associated with increased basal platelet activation and diminished pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
6
11
0
Order By: Relevance
“…On the other hand, the presence of glycoproteins, such as GPVI and vWF, is involved in thromboembolism and thromboinflammation, and other coagulopathies (23). However, recent studies have shown that platelets are indeed hyperactivated in COVID-19 but show reduced glycoprotein VI (GPVI) reactivity in COVID-19 patients (24), which is consistent with our results.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, the presence of glycoproteins, such as GPVI and vWF, is involved in thromboembolism and thromboinflammation, and other coagulopathies (23). However, recent studies have shown that platelets are indeed hyperactivated in COVID-19 but show reduced glycoprotein VI (GPVI) reactivity in COVID-19 patients (24), which is consistent with our results.…”
Section: Resultssupporting
confidence: 93%
“…Irrespective of the underlying mechanism(s), continuously activated platelets become exhausted, refractory, and have diversely impaired functionality. As a matter of fact, our findings are in agreement with an array of papers that describe the connection of platelet activation and subsequent dysfunction revealed in other pathological conditions, including a relatively new pathological condition known as vaccine-inducted thrombotic thrombocytopenia (VITT) [46][47][48][49][50][51][52][53].…”
Section: Discussionsupporting
confidence: 91%
“…Higher levels of PLA compared to healthy controls were found in the acute phase of COVID-19 [9] , [12] , [17] . Interestingly, COVID-19 patients with fatal outcome had significantly lower PLA levels compared to patients with uncomplicated disease [18] . It is, however, not clear whether increased PLA levels persist in COVID-19 convalescent.…”
Section: Discussionmentioning
confidence: 95%